(untitled) (The Research of Medical Science Review, 2024)
This study aimed to evaluate the association between maternal hypothyroidism and structural and functional heart abnormalities in fetuses among pregnant women presenting at a tertiary care hospital in Karachi, Pakistan. Conducted as a case-control study at thePediatric Cardiology Section of Liaquat National Hospital over one year (January to December 2022), the research involved two groups: mothers diagnosed with hypothyroidism undergoing fetal echocardiography (Group A) and mothers without hypothyroidism undergoing fetal echocardiography for other reasons (Group B). A standardized questionnaire collected data on maternal history of hypothyroidism, use of thyroid-replacement therapy, other medications during pregnancy, prenatal health status, child health, and demographics. SPSS version 25 was used for data analysis. A total of 66 mothers were enrolled in each group, and significant differences were observed in cardiac structural and functional measurements between the hypothyroid and non-hypothyroidgroups. However, no significant increase in congenital heart defects was noted in the hypothyroid group. The study concludes that maternal hypothyroidism is associated with structural and functional fetal heart abnormalities, emphasizing the importance of routinethyroid function screening and early fetal echocardiographic evaluations for pregnant women with hypothyroidism.